2004
DOI: 10.1007/s00402-004-0759-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cutting errors in total knee arthroplasty

Abstract: To minimize cutting errors, techniques and instruments are needed which enable a more stable fixation of the cutting blocks or even more appropriate preparation instruments. Using a computer-assisted technique, the surgeon is aware of cutting errors occurring at each point of the operation and will therefore be able to correct these errors during surgery, while he is not aware of those errors with the conventional TKA technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 17 publications
3
71
1
9
Order By: Relevance
“…Using traditional intramedullary alignment systems, deviations of up to 8°can occur in the femoral axis, depending on the size and length of the intramedullary guide [17]. Unstable cutting blocks and saw deviation during osteotomy have been shown to result in cutting errors [1,17]. In 2001, Mahaluxmivala et al showed that TKR alignment is improved with surgical experience [14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using traditional intramedullary alignment systems, deviations of up to 8°can occur in the femoral axis, depending on the size and length of the intramedullary guide [17]. Unstable cutting blocks and saw deviation during osteotomy have been shown to result in cutting errors [1,17]. In 2001, Mahaluxmivala et al showed that TKR alignment is improved with surgical experience [14].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted surgery provides the surgeon with continuous intraoperative feedback on implant alignment and cutting errors during all phases of TKR [1]. A reduction in cutting errors has been shown when a navigation system is used for TKR surgery [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, decisions regarding bony resection level are based on measurements taken using a traditional jig and rod, and thus, anterior notching and femoral component oversizing can be avoided. Unfortunately, the conventional technique is more inaccurate and inconsistent in terms of its component alignment ability than computer navigation [5,6]. In this paper, we describe a hybrid technique that combines the benefits of computer navigation and conventional TKA.…”
Section: Introductionmentioning
confidence: 99%